2015
DOI: 10.17795/ijep29796
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Helicobacter pylori Among Dyspeptic Patients Detected by Molecular Methods in a Teaching Hospital in Sri Lanka

Abstract: Background: Infection with Helicobacter pylori is considered as a major cause of chronic gastritis, peptic ulcer disease and gastric cancer. More than half of the world's population is infected with H. pylori. In Sri Lanka various groups have reported a prevalence ranging from 3% to 70% over the last decade. Objectives: The aim of this study was to determine the current proportion of H. pylori and risk factors for H. pylori infections. Patients and Methods:The study was a cross sectional, descriptive study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…One biopsy was used for PCR targeting the glmM gene to identify H. pylori infection. DNA extraction from gastric biopsies and PCR was performed as mentioned in Ubhayawardana et al 2015 [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One biopsy was used for PCR targeting the glmM gene to identify H. pylori infection. DNA extraction from gastric biopsies and PCR was performed as mentioned in Ubhayawardana et al 2015 [6].…”
Section: Methodsmentioning
confidence: 99%
“…H. pylori has been classi ed as a class I carcinogen for humans by the International Agency for Research on Cancer (IARC) monograph committee in 1994. Prevalence of H. pylori infection is an enigma in Sri Lanka ranging from 3 to 70% [4,5,6]. Further resistance to clarithromycin is a problem [7] which results in eradication failure with triple therapy [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…35 Recent studies conducted in Sri Lanka have reported a lower proportion of H. pylori among dyspeptic patients. 35,36,37 However, there is limited data available on the gastric microbial diversity and related complications such as dysplasia, gastric cancer and the effects on both health and disease in Sri Lanka.…”
Section: Diversity Of Gastric Microbiotamentioning
confidence: 99%
“…The role of TNF‐α polymorphisms in severity of H. pylori‐ associated disease has not been studied in Sri Lanka. Previous histological studies done in Sri Lanka have suggested that most H. pylori‐ infected patients have mild chronic gastritis and that development of gastric atrophy is not a significant problem. Multiple factors can contribute to a shift from mild to atrophic gastritis; however, host genetic factors can play a major role.…”
mentioning
confidence: 98%